ON THE EXISTENCE OF A MASS OF RESERVE AMONG HIGHER EDUCATION GRADUATES. ITS WEIGHT AND COMPOSITION IN ARGENTINA, 2010-2012 - Donaire, Ricardo Martín (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2017)
While the character of high education as a means of life is only available for the bourgeoisie and the wealthy strata of the petty bourgeoisie as a form to reproduce their class position, it also functions mainly as the grounds of a title under which these strata can appropriate a part of the social wealth. Thus, the loss of this character may be the indicator of some degree of decomposition in these strata. This situation is most openly presented in the possibility of unemployment among higher graduates, although it could also be extended to all those situations in which the categories that were trained to perform intellectual functions cannot be effectively employed in those activities. Can this situation be associated with a process of proletarianization? Guided by this question, this paper presents a series of considerations based on an analysis of the weight and composition of higher education graduates in Argentina, particularly those who are not included in occupations traditionally attributed to the wealthy petty bourgeoisie. The data comes from the processing of information from the official Annual Urban Household Survey 2010 and 2012.